FORMASI SPIRITUAL DAN PERKEMBANGAN EMOSI ANAK USIA DINI DALAM PERSPEKTIF PSIKOLOGI KRISTEN - Fredik Melkias Boiliu (Institut Kristen Teologi REAL Batam, 2026)
Early childhood emotional development is inseparable from the spiritual formation process that shapes the way children interpret themselves, relationships, and the surrounding environment. However, in the practice of early childhood education in Indonesia, the spiritual dimension is often reduced to ritual activities, without a deep connection to the development of children's emotions. This article aims to examine the relationship between spiritual formation and early childhood emotional development from a Christian psychological perspective. This study uses a literature study method by analyzing the literature on developmental psychology, Christian psychology, and theology of children's education. The results of the study show that spiritual formations that are relational, contextual, and consistent contribute significantly to emotional regulation, security, empathy, and emotional resilience in early childhood. The discussion affirms that in Christian psychology, emotions are understood as the initial space of the child's experience of faith, where love, acceptance, and secure attachment become the foundation of spirituality. The implications of this study show that early childhood Christian education in Indonesia needs to integrate emotional mentoring and spiritual formation holistically, by involving the active role of teachers and parents as value mediators and role models of faith in daily life. Keywords: early childhood; spiritual formation; emotional development; Christian psychology Abstrak Perkembangan emosi anak usia dini tidak dapat dipisahkan dari proses formasi spiritual yang membentuk cara anak memaknai diri, relasi, dan lingkungan sekitarnya. Namun, dalam praktik pendidikan anak usia dini di Indonesia, dimensi spiritual sering kali direduksi menjadi aktivitas ritual, tanpa keterkaitan yang mendalam dengan perkembangan emosi anak. Artikel ini bertujuan untuk mengkaji relasi antara formasi spiritual dan perkembangan emosi anak usia dini dalam perspektif psikologi Kristen. Penelitian ini menggunakan metode studi pustaka dengan menganalisis literatur psikologi perkembangan, psikologi Kristen, serta teologi pendidikan anak. Hasil kajian menunjukkan bahwa formasi spiritual yang bersifat relasional, kontekstual, dan konsisten berkontribusi signifikan terhadap regulasi emosi, rasa aman, empati, dan ketahanan emosional anak usia dini. Pembahasan menegaskan bahwa dalam psikologi Kristen, emosi dipahami sebagai ruang awal pengalaman iman anak, di mana kasih, penerimaan, dan kelekatan aman menjadi fondasi spiritualitas. Implikasi penelitian ini menunjukkan bahwa pendidikan anak usia dini Kristen di Indonesia perlu mengintegrasikan pendampingan emosi dan formasi spiritual secara holistik, dengan melibatkan peran aktif guru dan orang tua sebagai mediator nilai dan teladan iman dalam kehidupan sehari-hari. Kata Kunci: anak usia dini; formasi spiritual; perkembangan emosi; psikologi Kristen